2012
DOI: 10.1093/humrep/des092
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human phospholipase C zeta 1 induces intracellular calcium oscillations and oocyte activation in mouse and human oocytes

Abstract: Repeated [Ca(2+)](i) oscillations and oocyte activation were induced in mouse and human oocytes by microinjection of recombinant hPLCZ1 synthesized in E. Coli. Injection of recombinant protein could thus provide a biological solution for inducing artificial activation of oocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 65 publications
1
61
0
1
Order By: Relevance
“…We have recently demonstrated that NusA is an effective fusion protein partner for human PLCz, significantly increasing the expression of soluble PLCz protein in E. coli, as well as enhancing the stability of the purified protein over time . Expression of active recombinant human PLCz protein has also been reported by other groups (Kashir et al, 2011;Yoon et al, 2012). Following expression of NusA-PLCz fusion proteins in E. coli and purification by Ni-NTA affinity chromatography, the recombinant proteins were characterized.…”
Section: Enzymatic Characterization Of Human Mouse and Human/mouse Pmentioning
confidence: 80%
“…We have recently demonstrated that NusA is an effective fusion protein partner for human PLCz, significantly increasing the expression of soluble PLCz protein in E. coli, as well as enhancing the stability of the purified protein over time . Expression of active recombinant human PLCz protein has also been reported by other groups (Kashir et al, 2011;Yoon et al, 2012). Following expression of NusA-PLCz fusion proteins in E. coli and purification by Ni-NTA affinity chromatography, the recombinant proteins were characterized.…”
Section: Enzymatic Characterization Of Human Mouse and Human/mouse Pmentioning
confidence: 80%
“…We emphasize the importance of the semiquantitative assay we developed to determine PLC activity. (73,74) to infer PLC activity. Our method allowed us to determine that PIP 2 hydrolysis, induced by ARF6, decreased when DAG was sequestered by the C1 domain of Munc13-1.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence support the role of PLCζ in inducing Ca 2+ oscillation in oocytes; microinjection of either PLCζ complementary RNA (cRNA) or recombinant protein into bovine and murine oocytes induces Ca 2+ oscillations and oocyte activation [8,[12][13][14][15][16]. Moreover, injection of human PLCζ cRNA and recombinant PLCζ protein into human oocytes triggers calcium oscillations and development to the blastocyst stage [9,17]. On the other hand, injection of domain-deletion PLCζ constructs leads to the inability of the protein to generate Ca 2+ oscillations, while reduction of PLCζ expression by RNA interference during Capsule PLCζ seems to be a necessary but not sufficient factor in determining the molecular pathway involved in oocyte activation.…”
Section: Introductionmentioning
confidence: 99%